The Integration of Artificial Intelligence (AI) Technology into Teaching Strategies Among Educators in Vocational Colleges of Johor - Ahmad Rizal Madar; Saidi, Ezza Elyani (Research and Innovation in Technical and Vocational Education and Training, 2025)
The rapid advancement of technology, particularly in the field of artificial intelligence (AI), has paved the way for transformation in the educational sector, including vocational education. This study aims to explore the professionalism of Vocational College (KV) educators in Johor in integrating AI technology into teaching strategies. Specifically, the objectives are to identify the levels of knowledge, professional support needs, and challenges faced by KV educators, as well as to examine the relationships among these three variables and their influence on educators’ professionalism.This quantitative study employed a survey method involving 148 educators from three Vocational Colleges in Johor, namely KV Muar, KV Batu Pahat, and KVSegamat. The data collected were analysed using descriptive statistics (mean and standard deviation) and inferential statistics (Spearman correlation) to address all research objectives. Findings indicated that the levels of knowledge and professional support needs were moderately high, whereas the challenges faced by educators were high. Inferential analysis revealed a significant relationship between knowledge and professional support needs, and between professional support needs and challenges. However, no significant relationship was found between knowledge and challenges.The implications of the study highlight that successful integration of AI in teaching does not rely solely on educators’ knowledge, but also on sustained professional support and the institution’s capacity to address implementation barriers. Therefore, targeted training, technical guidance, and infrastructural support are essential in strengthening educators’ professionalism in the digital education era. In conclusion, this study contributes to a deeper understanding of the readiness of TVET institutions to embrace technological transformation in education, and provides a solid foundation for future research and educational policy planning.